2018
DOI: 10.3758/s13428-017-1001-8
|View full text |Cite
|
Sign up to set email alerts
|

On the predictive validity of various corpus-based frequency norms in L2 English lexical processing

Abstract: The predictive validity of various corpus-based frequency norms in first-language lexical processing has been intensively investigated in previous research, but less attention has been paid to this issue in second-language (L2) processing. To bridge the gap, in the present study we took English as a case in point and compared the predictive power of a large set of corpus-based frequency norms for the performance of an L2 English visual lexical decision task (LDT). Our results showed that, in general, the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…From a more general standpoint, a limitation of this data-driven approach to correcting pupil data is its implicit assumption that pupil size does not actually depend on gaze position and that any observed relationship is consequently artifactual. As Mathôt, Fabius, Van Heusden, & Van der Stigchel (2018) point out, this assumption may be flawed. For example, if participants are required to make uncomfortable eye movements to foveate extreme parts of the screen, the pupil may dilate because of the mental and physical effort involved with this action.…”
Section: Discussionmentioning
confidence: 99%
“…From a more general standpoint, a limitation of this data-driven approach to correcting pupil data is its implicit assumption that pupil size does not actually depend on gaze position and that any observed relationship is consequently artifactual. As Mathôt, Fabius, Van Heusden, & Van der Stigchel (2018) point out, this assumption may be flawed. For example, if participants are required to make uncomfortable eye movements to foveate extreme parts of the screen, the pupil may dilate because of the mental and physical effort involved with this action.…”
Section: Discussionmentioning
confidence: 99%
“…systematic error) for the remaining 68 participants by measuring the difference between the average fixation location and the calibration point (averaged over participants and calibration points). The systematic error was found to be 0.65o n average (for more details, see [53]). We concluded that data quality for the remaining 68 participants was adequate for the subsequent analyses, because the average systematic error was approximately three times as low as the average AOI span of 2.035˚(see Method section).…”
Section: Eye-tracking Data Quality Assessmentmentioning
confidence: 99%
“…When the operator was ready, the participant would take place in the chinrest and the black cloth was draped over the participant. Reprinted from [53] with permission.…”
Section: General Proceduresmentioning
confidence: 99%
“…Traditionally, estimating LCDMs refers to the expectation maximization (EM) algorithm (Bock and Aitkin, 1981 ) that maximizes the marginal likelihood; this is the most commonly-seen algorithm in the CDM literature. In addition to the EM algorithm, Markov chain Monte Carlo (MCMC) techniques can be, theoretically, used to estimate the LCDM, but to date its application remains upon simpler CDMs such as the DINA model (da Silva et al, 2017 ; Jiang and Carter, 2018a ). This study focuses on the EM algorithm due to its practicality and popularity.…”
Section: Lcdm Estimationmentioning
confidence: 99%
“…To compare the estimates with other estimation approaches, we also implemented a Bayesian technique-Hamiltonian Monte Carlo-to the analysis by adopting uninformative priors for both item parameters and the class membership probability: the mean and standard deviation for item parameters were 0 and 20, while the Dirichelet prior parameters were all set to 1 (see Jiang and Carter, 2018a for details). The correlations of item parameter estimates were relatively high: 0.77, 0.84, and 0.69 for intercept, main effect, and interaction effects.…”
Section: Real Data Applicationmentioning
confidence: 99%